High-Amplitude Gastric Contractions following Laparoscopic Sleeve Gastrectomy - Jerry Zhou; Carolyn Jameson; Vincent Ho (Case Reports in Surgery)
A proportion of laparoscopic sleeve gastrectomy patients experience symptoms of regurgitation and epigastric pain postoperation. The appearance of gastric sleeve contractions has been documented but its implications have not been adequately investigated. This case describes a 61-year-old female following laparoscopic sleeve gastrectomy. The patient underwent high-resolution impedance esophageal manometry that identified compartmentalized pressurization leading to propagating contractions throughout the gastric sleeve. Combined treatment with calcium channel blockers and gastric sleeve dilation relieved all symptoms. This case highlights the application of high-resolution impedance esophageal manometry to assess motor function and bolus transit in patients following laparoscopic sleeve gastrectomy.